AN ANALYSIS OF THE CORRELATION BETWEEN TEACHERS’ TEACHING SKILLS AND STUDENTS’ ACHIEVEMENT IN SOCIAL STUDIES AT MTS DARUL AMAN TEGAL SELAGALAS - Malthuf, Muhammad; Riqiya, Hilma (SOCIETY, 2025)
Teaching skills constitute a critical determinant of instructional effectiveness, encompassing a teacher’s ability to guide learners through organized and interactive learning processes. These skills include the capacity to open and close lessons effectively, explain concepts clearly, pose stimulating questions, provide reinforcement, manage classroom dynamics, and apply varied teaching methods suited to learners’ needs. This study aimed to examine the relationship between teachers’ teaching skills and students’ academic achievement in Social Studies among Grade VIII students at MTs Darul Aman Tegal Selagalas, as well as to identify instructional strategies that effectively enhance students’ learning outcomes. A mixed-methods approach employing the concurrent embedded model was used, involving 173 students as respondents. Data were collected through questionnaires, interviews, and documentation, then analyzed quantitatively using simple linear regression and qualitatively through thematic analysis. The findings revealed a significant positive correlation (r = 0.60) between teachers’ teaching skills and students’ academic achievement, indicating that 60% of the variance in learning outcomes could be explained by teaching skills. The study further identified that classroom management and variation in instructional strategies were among the least mastered competencies, affecting students’ engagement and comprehension. The study concludes that teachers’ pedagogical skills play a decisive role in shaping students’ learning performance in Social Studies. It recommends continuous professional development through workshops and subject-based teacher associations (MGMP) to strengthen instructional competence. Enhancing these teaching skills is expected to foster an engaging and effective learning environment, ultimately improving academic achievement and the overall quality of education. Keywords: Teaching Skills, Social Studies Teachers, Learning Achievement, Instructional Strategies